2015
DOI: 10.1007/s40263-015-0238-y
|View full text |Cite
|
Sign up to set email alerts
|

Fertility, Pregnancy and Childbirth in Patients with Multiple Sclerosis: Impact of Disease-Modifying Drugs

Abstract: In recent decades, pregnancy-related issues in multiple sclerosis (MS) have received growing interest. MS is more frequent in women than in men and typically starts during child-bearing age. An increasing number of disease-modifying drugs (DMDs) for the treatment of MS are becoming available. Gathering information on their influences on pregnancy-related issues is of crucial importance for the counselling of MS patients. As for the immunomodulatory drugs (interferons and glatiramer acetate), accumulating evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 139 publications
(181 reference statements)
0
66
0
3
Order By: Relevance
“…Endocrinological studies have shown differences in the levels of sex hormones and the gonadotropins that regulate their production between women with MS compared to women of the general population [9]. Significantly higher levels of folliclestimulating hormone (FSH) and luteinizing hormone (LH) have been recorded, as well as significantly lower levels of estrogen in the early follicular phase of the menstrual cycle [10,11].…”
Section: Hormonal Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Endocrinological studies have shown differences in the levels of sex hormones and the gonadotropins that regulate their production between women with MS compared to women of the general population [9]. Significantly higher levels of folliclestimulating hormone (FSH) and luteinizing hormone (LH) have been recorded, as well as significantly lower levels of estrogen in the early follicular phase of the menstrual cycle [10,11].…”
Section: Hormonal Effectsmentioning
confidence: 99%
“…Fingolimod Fingolimod (trade name Gilenya®) acts to reduce the number of lymphocytes present in the central nervous system by preventing their release from lymph nodes. Rat experiments have shown no effect on female fertility upon administration of fingolimod, but they exerted teratogenic effects, the most common being congenital heart defects [9]. The rate of spontaneous abortion in women using fingolimod is higher than that of the general population [25].…”
Section: Effect Of Dmt On Pregnancymentioning
confidence: 99%
See 3 more Smart Citations